-x(+13)=-2(x-2)

Simple and best practice solution for -x(+13)=-2(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x(+13)=-2(x-2) equation:



-x(+13)=-2(x-2)
We move all terms to the left:
-x(+13)-(-2(x-2))=0
We add all the numbers together, and all the variables
-x13-(-2(x-2))=0
We add all the numbers together, and all the variables
-1x^13-(-2(x-2))=0
We calculate terms in parentheses: -(-2(x-2)), so:
-2(x-2)
We multiply parentheses
-2x+4
Back to the equation:
-(-2x+4)
We do not support expression: x^13

See similar equations:

| 14.x=0 | | 9^(x)+3^(x+1)=28 | | 4k-4(9-4k)=5k+5k | | 8=  -2n | | 5+6x=41+3x | | 2x+(-9+x)=12 | | 2x-7=7x-7 | | 8z=6z+2 | | x+11/10=109/15 | | 13=m-8 | | (7x-4)=(8x-27)° | | 1/3x+10=3/5x+0 | | x-7+34=40 | | 9r-7=180 | | x-7+34=4 | | 2w-8=1+w | | 1=a/13-6 | | (7x-1)=(5x-23 | | 8x+10+5x+1=180 | | 8r+6=180 | | -9(-x+1)+3x=6x+45 | | (X+6)=(4x-45) | | 6x−4=8 | | 5^3x=3000 | | 180-x=6*(90-x)+40. | | 8x+33=10x+17 | | −2x=  −4 | | 3x-5(x-3)=-2+3x-23 | | -1x/4+8=3/2-5x | | (x+53)+(x+68)+75=180 | | 5(x+9)-5(x-7)=73 | | -3c-4+6=3c+8 |

Equations solver categories